The Complexity of the Tumor Microenvironment and Its Role in Acute Lymphoblastic Leukemia: Implications for Therapies - Simioni, Carolina; Conti, Ilaria; Varano, Gabriele; Brenna, Cinzia; Costanzi, Eva; Neri, Luca M. (Frontiers in Oncology, 2021)
The microenvironment that surrounds a tumor, in addition to the tumor itself, plays an important role in the onset of resistance to molecularly targeted therapies. Cancer cells and their microenvironment interact closely between them by means of a molecular communication that mutually influences their biological characteristics and behavior. Leukemia cells regulate the recruitment, activation and program of the cells of the surrounding microenvironment, including those of the immune system. Studies on the interactions between the bone marrow (BM) microenvironment and Acute Lymphoblastic Leukemia (ALL) cells have opened a scenario of potential therapeutic targets which include cytokines and their receptors, signal transduction networks, and hypoxia-related proteins. Hypoxia also enhances the formation of new blood vessels, and several studies show how angiogenesis could have a key role in the pathogenesis of ALL. Knowledge of the molecular mechanisms underlying tumor-microenvironment communication and angiogenesis could contribute to the early diagnosis of leukemia and to personalized molecular therapies. This article is part of a Special Issue entitled: Innovative Multi-Disciplinary Approaches for Precision Studies in Leukemia edited by Sandra Marmiroli (University of Modena and Reggio Emilia, Modena, Italy) and Xu Huang (University of Glasgow, Glasgow, United Kingdom).